S100A9 and HMGB1 orchestrate MDSC-mediated immunosuppression in melanoma through TLR4 signaling - Özbay Kurt, Feyza Gül; Cicortas, Beatrice-Ana; Balzasch, Bianca M.; Torre, Carolina de la; Ast, Volker; Tavukçuoğlu Demir, Ece; Ak, Cagla; Wohlfeil, Sebastian A.; Cerwenka, Adelheid; Utikal, Jochen; Umansky, Viktor (Journal for ImmunoTherapy of Cancer, 2024)
Background Immunotherapies for malignant melanoma are challenged by the resistance developed in a significant proportion of patients. Myeloid-derived suppressor cells (MDSC), with their ability to inhibit antitumor T-cell responses, are a major contributor to immunosuppression and resistance to immune checkpoint therapies in melanoma. Damage-associated molecular patterns S100A8, S100A9, and HMGB1, acting as toll like receptor 4 (TLR4) and receptor for advanced glycation endproducts (RAGE) ligands, are highly expressed in the tumor microenvironment and drive MDSC activation. However, the role of TLR4 and RAGE signaling in the acquisition of MDSC immunosuppressive properties remains to be better defined. Our study investigates how the signaling via TLR4 and RAGE as well as their ligands S100A9 and HMGB1, shape MDSC-mediated immunosuppression in melanoma. - Methods MDSC were isolated from the peripheral blood of patients with advanced melanoma or generated in vitro from healthy donor-derived monocytes. Monocytes were treated with S100A9 or HMGB1 for 72 hours. The immunosuppressive capacity of treated monocytes was assessed in the inhibition of T-cell proliferation assay in the presence or absence of TLR4 and RAGE inhibitors. Plasma levels of S100A8/9 and HMGB1 were quantified by ELISA. Single-cell RNA sequencing (scRNA-seq) was performed on monocytes from patients with melanoma and healthy donors. - Results We showed that exposure to S100A9 and HMGB1 converted healthy donor-derived monocytes into MDSC through TLR4 signaling. Our scRNA-seq data revealed in patient monocytes enriched inflammatory genes, including S100 and those involved in NF-κB and TLR4 signaling, and a reduced major histocompatibility complex II gene expression. Furthermore, elevated plasma S100A8/9 levels correlated with shorter progression-free survival in patients with melanoma. - Conclusions These findings highlight the critical role of TLR4 and, to a lesser extent, RAGE signaling in the conversion of monocytes into MDSC-like cells, underscore the potential of targeting S100A9 to prevent this conversion, and highlight the prognostic value of S100A8/9 as a plasma biomarker in melanoma.